Translaminar activity of different insecticides against Bemisia tabaci - DUMRA, NEERU; ROLANIA, KRISHNA; YADAV, SURENDER SINGH; KUMARI, SONU (The Indian Journal of Agricultural Sciences, 2023)
One of the main mechanisms of action for many insecticides is translaminar redistribution or local systemic. The present study was carried out at Chaudhary Charan Singh Haryana Agricultural University, Hisar, Haryana during 2019 and 2020 to investigate the translaminar activity of different insecticides having different doses and sprays on treated brinjal plant having Bemisia tabaci (Gennadius) nymphs. Different treatments, i.e. diafenthiuron 50% WP (150, 210, and 300 g a.i./ha), fenpropathrin 30% EC (50, 70, and 100 g a.i./ha), thiamethoxam 25% WG (25, 35, and 50 g a.i./ha), and deltamethrin 2.8% EC (7.5, 10.5 and 15 g a.i./ha) were frequently sprayed on brinjal plants (var. Hisar Shyamal) growing in pots. Insecticides effectiveness was measured through nymphal mortality of B. tabaci (whitefly). Similar study was conducted in 2020 to ensure reliability of results. The results revealed that, almost similar trends were obtained during 2019 and 2020, hence proving reliability. Among all tested insecticides, maximum translaminar effect was observed in thiamethoxam 25% WG treated plant at 50 g a.i./ha (50.72% nymphal mortality). Whereas, deltamethrin 2.8% EC treated plant at 15 g a.i./ha showed minimum translaminar effect (0.63% nymphal mortality) as compared to other treatments. Translaminar effect of leaves treated with diafenthiuron 50% WP and fenpropathrin 30% EC was found at par with each other. Nymphal mortality is low in sub-lethal doses of insecticides as compared to lethal doses. It can be concluded that resistance may develop due to sub-lethal doses of insecticides. Farmers and agricultural experts would benefit from this study’s findings.